2000
DOI: 10.2143/ac.55.6.2005765
|View full text |Cite
|
Sign up to set email alerts
|

Recent fidings on return to work after an acute myocardial infarction or coronary artery bypass grafting

Abstract: Return to work remains one of the main issues in cardiac rehabilitation after AMI or CABG. If resumption is sufficiently emphasized, a high success rate can be achieved. This approach should include a psychosocial strategy starting already during hospitalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
1
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 0 publications
3
64
1
5
Order By: Relevance
“…Chung et al (25) described two cohort studies (Nashville/Jyväs-kylä) in one article, but we presented the results as two studies. Also the results of the two cohorts of Boudrez et al (19) are described separately (IHD with and without (IHD with and without surgery). .…”
Section: Selection and Methodological �Uality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Chung et al (25) described two cohort studies (Nashville/Jyväs-kylä) in one article, but we presented the results as two studies. Also the results of the two cohorts of Boudrez et al (19) are described separately (IHD with and without (IHD with and without surgery). .…”
Section: Selection and Methodological �Uality Assessmentmentioning
confidence: 99%
“…Six studies found a positive relation (30,(45)(46)(47)(48)(49) and one article found no relation (49) between depression and work disability. The level of somatic complaints was found to have a positive relation with work disability in three articles (19,28,50), while two articles found no effect (19,46). For employees with IHD, Q wave in cases with acute myocardial infarction (yes versus no) (34,51) and chest pain (yes versus no) (32,52,53) were found to be moderate positive prognostic factors for work disability.…”
Section: Prognostic Factors For Work Disabilitymentioning
confidence: 95%
See 3 more Smart Citations